Alcohol consumption and breast cancer risk among women in three sub-Saharan African countries. - Frank Qian; Temidayo Ogundiran; Ningqi Hou; Paul Ndom; Antony Gakwaya; Johashaphat Jombwe; Imran Morhason-Bello; Clement Adebamowo; Adeyinka Ademola; Oladosu Ojengbede; Olufunmilayo I Olopade; Dezheng Huo (PLoS ONE, 2014)
Alcohol drinking is linked to the development of breast cancer. However, there is little knowledge about the impact of alcohol consumption on breast cancer risk among African women.We conducted a case-control study among 2,138 women with invasive breast cancer and 2,589 controls in Nigeria, Cameroon, and Uganda from 1998 to 2013. A structured questionnaire was used to collect information on alcohol consumption, defined as consuming alcoholic beverages at least once a week for six months or more. Logistic regression was used to estimate adjusted odds ratio (aOR) and 95% confidence interval (CI).Among healthy controls, the overall alcohol consumption prevalence was 10.4%, and the prevalence in Nigeria, Cameroon, and Uganda were 5.0%, 34.6%, and 50.0%, respectively. Cases were more likely to have consumed alcohol (aOR = 1.62, 95% CI: 1.33-1.97). Both past (aOR = 1.54; 95% CI: 1.19-2.00) and current drinking (aOR = 1.71; 95% CI: 1.30-2.23) were associated with breast cancer risk. A dose-response relationship was observed for duration of alcohol drinking (P-trend <0.001), with 10-year increase of drinking associated with a 54% increased risk (95% CI: 1.29-1.84).We found a positive relationship between alcohol consumption and breast cancer risk, suggesting that this modifiable risk factor should be addressed in breast cancer prevention programs in Africa.